Serum immunoreactive trypsin concentrations in diabetic children. Issue 9 (September 1980) - Moffat, A; Marks, V; Gamble, D R
Abstract : Serum immunoreactive trypsin (SIT) concentrations measured in 616 children with diabetes of recent onset were low, in both boys and girls, in comparison with reference ranges established in patients with non-diabetic, non-infectious illnesses. The mean SIT concentration was 60% of the mean reference level in children tested within three weeks of the onset of diabetes, and about 40% in patients tested six months after the onset of diabetes. Very low SIT levels were found in about 10% of patients, most of whom had no measurable SIT by the assay procedure employed. These very low SIT concentrations were more frequent in older children aged 6-15 years, and in children tested at about 5-6 months after onset. Repeat tests on some of the children showed that the very low SIT levels were generally present for only a limited period.